Analisis Pengaruh Pemanfaatan Sistem Informasi Akuntansi dan Laporan Keuangan terhadap Kinerja Umkm: Studi Kasus di Kota Cepu - Aprinka, Alvina (SENTRI: Jurnal Riset Ilmiah, 2026)
This research examines whether the application of Accounting Information Systems (AIS) and the utilization of financial reports influence the business performance of Micro, Small, and Medium Enterprises (MSMEs) operating in Cepu, Blora Regency, Central Java. A quantitative design was applied through a survey-based approach. The study used primary information obtained from questionnaires completed by 90 MSME proprietors who were chosen through purposive sampling according to specified eligibility requirements. Multiple regression analysis was conducted after the dataset satisfied the validity, reliability, and classical assumption assessments. The results are anticipated to provide practical guidance for MSME operators concerning the role of AIS implementation and financial report usage in strengthening enterprise performance.